2013
DOI: 10.2460/javma.242.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and treatment of transitional cell carcinoma of the abdominal wall in dogs: 24 cases (1985–2010)

Abstract: Results suggested that ABWTCC is uncommon, but once TCC becomes established and clinically detectable in the abdominal wall, it carries a poor prognosis. It is crucial to minimize risk of TCC seeding at surgery. Percutaneous sampling of TCC should be avoided. Uroplakin III is commonly expressed in ABWTCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 16 publications
(27 reference statements)
1
45
0
Order By: Relevance
“…Needle tract implantation overall is considered rare 23. It has been reported that abdominal wall TCC occurred in 6/367 patients having had ultrasound‐guided fine‐needle aspiration of the prostate gland or urinary bladder 24. This number excluded dogs that had a previous cystotomy performed.…”
Section: Discussionmentioning
confidence: 99%
“…Needle tract implantation overall is considered rare 23. It has been reported that abdominal wall TCC occurred in 6/367 patients having had ultrasound‐guided fine‐needle aspiration of the prostate gland or urinary bladder 24. This number excluded dogs that had a previous cystotomy performed.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer, also called transitional cell carcinoma (TCC), or urothelial carcinoma (UC) is yet another tumour that affects both humans and their pet dogs [112,113]. In humans, environmental exposure, including tobacco smoke, is a major risk factor for UC.…”
Section: (C) Bladder Cancermentioning
confidence: 99%
“…Thus, studying canine osteosarcoma and the application of new techniques will help reveal the misexpression of other genes involved in human osteosarcoma. Bladder cancer, also known as transitional cell carcinoma (TCC) or urothelial carcinoma (UC) and affects both canines and humans (Higuchi et al, 2013;Park and Hahn, 2014). TCC comprises about 2% of all malignant tumours in dogs (Meuten and Mueten, 2014).…”
Section: Http://wwwopenveterinaryjournalcom F Sultan and Ba Ganaiementioning
confidence: 99%